2017
DOI: 10.1016/j.omtn.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Viral Vector-Mediated mTOR Inhibition by Short Hairpin RNA Suppresses Laser-Induced Choroidal Neovascularization

Abstract: Choroidal neovascularization (CNV) is the defining characteristic feature of the wet subtype of age-related macular degeneration (AMD) and may result in irreversible blindness. Based on anti-vascular endothelial growth factor (anti-VEGF), the current therapeutic approaches to CNV are fraught with difficulties, and mammalian target of rapamycin (mTOR) has recently been proposed as a possible therapeutic target, although few studies have been conducted. Here, we show that a recombinant adeno-associated virus-del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 53 publications
(72 reference statements)
3
33
0
Order By: Relevance
“…The experimental virus vectors, rAAV2-shmTOR-GFP (previously rAAV-mTOR shRNA-enhanced GFP (EGFP)) and rAAV2-shCon-GFP (previously rAAV-scrambled shRNA-EGFP), were prepared as previously described. 20 Briefly, the mTOR-inhibiting shRNA (5'-GAAUGUUGACCAAUGCUAU-3') or control shRNA (5'-AUUCUAUCACUAGCGUGAC-3'), both under the control of an H1 promoter, were inserted alongside an EGFP expression cassette driven by the cytomegalovirus promoter into a self-complementary AAV2 vector. All of the virus vectors used in this study were obtained from CdmoGen Co., Ltd. (Cheongju, Korea).…”
Section: Preparation Of Virus Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental virus vectors, rAAV2-shmTOR-GFP (previously rAAV-mTOR shRNA-enhanced GFP (EGFP)) and rAAV2-shCon-GFP (previously rAAV-scrambled shRNA-EGFP), were prepared as previously described. 20 Briefly, the mTOR-inhibiting shRNA (5'-GAAUGUUGACCAAUGCUAU-3') or control shRNA (5'-AUUCUAUCACUAGCGUGAC-3'), both under the control of an H1 promoter, were inserted alongside an EGFP expression cassette driven by the cytomegalovirus promoter into a self-complementary AAV2 vector. All of the virus vectors used in this study were obtained from CdmoGen Co., Ltd. (Cheongju, Korea).…”
Section: Preparation Of Virus Vectorsmentioning
confidence: 99%
“…19 Previously, we explored the therapeutic efficacy of the shRNA-containing virus vector in a laser-induced mouse model of choroidal neovascularization, which models the wet subtype of age-related macular degeneration, and it was shown to reduce the extent to which neovascularization occurred. 20 To see if these effects were able to be recapitulated in an animal model of pathological retinal angiogenesis, we injected a rat oxygen-induced retinopathy (OIR) model with the virus vector, renamed recombinant adeno-associated virus expressing an shRNA (rAAV2-shmTOR-GFP), to explore its suitability as a potential gene therapeutic for neovascular retinal conditions. We show here that the direct inhibition of mTOR in vivo is antiangiogenic and that rAAV2-shmTOR-GFP reduces arterial tortuosity in the hypoxic retina, while also possessing anti-inflammatory and antiapoptotic capabilities.…”
mentioning
confidence: 99%
“…Recently, our group demonstrated the feasibility of gene therapy for nAMD using AAV-mTOR shRNA. 14 Intravitreal administration of AAV2 facilitates targeting of CNV lesions, but we did not demonstrate vector transduction of specific retinal cell types. Because pathologic conditions of the retina may alter the vector transduction of retinal cells, there exists a great necessity to evaluate the transduction efficiency of viral vectors in the diseased retina.…”
Section: Discussionmentioning
confidence: 55%
“…We recently demonstrated that AAV-mediated mammalian target of rapamycin (mTOR) inhibition by short hairpin RNA (shRNA) (AAV-mTOR shRNA) resulted in increased autophagy and suppressed choroidal neovascularization (CNV) in the mouse retina, suggesting potential for nAMD gene therapy. 14 Additionally, intravitreal administration of AAV2 resulted in transduction of CD31 + cells in CNV lesions. However, only AAV2 was evaluated in that study.…”
Section: Introductionmentioning
confidence: 99%
“…For a negative control, GFP gene was inserted to generate rAAV2-GFP. rAAV2 was produced using a triple cotransfection method as described previously, 11 supplied by CdmoGen Co., Ltd. (Cheongju, Korea).…”
Section: Cell Culture and Preparation Of Raav2smentioning
confidence: 99%